Negative electrode material for lithium ion secondary battery, negative electrode for lithium ion secondary battery, and lithium ion secondary battery
By using silicon particles with specific particle size and oxygen content and forming an oxidation coating of appropriate thickness on their surfaces, the problem of degradation of cycling characteristics of lithium-ion secondary batteries is solved, and higher battery performance and service life are achieved.
Patent Information
- Application Number
- CN202380062353.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-13
- Publication Date
- 2025-04-08
AI Technical Summary
The circulation characteristics of lithium-ion secondary batteries are affected by the volume expansion of the negative electrode active material, resulting in a decline in battery performance.
Silicon particles containing a specific particle size and oxygen content range are used as the negative electrode material, and an oxidation coating of appropriate thickness is formed on their surface to reduce volume expansion and electrolyte decomposition.
It significantly improves the circulation characteristics of lithium-ion secondary batteries, extends the service life of the battery, and improves the overall performance of the battery.
Smart Images

Figure CN119790509A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a negative electrode material for a lithium ion secondary battery, a negative electrode for a lithium ion secondary battery and a lithium ion secondary battery. Background Art
[0002] Lithium-ion secondary batteries are also widely used as a power source for mobile devices such as mobile phones and laptop computers, and hybrid vehicles.
[0003] The capacity of lithium-ion secondary batteries depends mainly on the active material of the electrode. Graphite is generally used as the negative electrode active material, but a higher capacity negative electrode active material is required. Therefore, silicon (Si), which has a much larger theoretical capacity than graphite (372 mAh / g), has attracted much attention.
[0004] The negative electrode active material containing silicon is accompanied by a large volume expansion during charging. The volume expansion of the negative electrode active material becomes the reason for the reduction of the cycle characteristics of the battery. If the volume expansion of the negative electrode active material occurs, for example, the negative electrode active material is damaged, or the conductive path between the negative electrode active materials is cut off, or peeling occurs at the interface between the negative electrode active material layer and the collector, or cracks occur in the SEI (Solid Electrolyte Interphase, solid electrolyte membrane) coating, resulting in decomposition of the electrolyte, etc. These reduce the cycle characteristics of the battery.
[0005] For example, Patent Document 1 describes that the cycle characteristics can be improved by regulating the aspect ratio of silicon particles and the tilt angle of silicon particles with respect to a current collector.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2019-149333 Summary of the invention
[0009] The technical problem that the invention is intended to solve
[0010] Cycle characteristics are important parameters, and it is desired to improve cycle characteristics using a method other than the method described in Patent Document 1.
[0011] The present disclosure has been made in view of the above-mentioned problems, and an object of the present disclosure is to provide a lithium ion secondary battery having excellent cycle characteristics.
[0012] Means for solving technical problems
[0013] In order to solve the above technical problems, the following means are provided.
[0014] (1) The negative electrode material for a lithium ion secondary battery provided in the first embodiment contains silicon particles. The average particle size of the silicon particles is greater than 0.1 μm and less than 10 μm, and the oxygen content is greater than 0.1 wt% and less than 8 wt%. When the surface of the silicon particles is analyzed using X-ray photoelectron spectroscopy, the cumulative intensity ratio obtained by dividing the cumulative intensity of the peak of SiO2 by the cumulative intensity of the peak of Si is greater than 0.4 and less than 3.0.
[0015] (2) In the negative electrode material for a lithium ion secondary battery of the above aspect, the cumulative intensity ratio may be 0.6 or more and 1.5 or less.
[0016] (3) In the negative electrode material for a lithium ion secondary battery of the above aspect, the silicon particles may have an average circularity of 0.920 to 0.985, and an average aspect ratio of 0.80 to 0.97.
[0017] (4) In the negative electrode material for lithium ion secondary batteries of the above aspect, the silicon particles may have an oxide film on the surface. The oxide film may have a thickness of 50 nm to 500 nm.
[0018] (5) In the negative electrode material for a lithium ion secondary battery of the above aspect, the oxide film may have a thickness of 100 nm to 300 nm.
[0019] (6) In the negative electrode material for a lithium ion secondary battery of the above aspect, the average particle size of the silicon particles may be 1 μm or more and 7 μm or less.
[0020] (7) In the negative electrode material for a lithium ion secondary battery of the above aspect, the silicon content of the silicon particles may be 97% or more and 99% or less.
[0021] (8) A second aspect provides a negative electrode for a lithium ion secondary battery comprising the negative electrode material for a lithium ion secondary battery of the above aspect.
[0022] (9) A third aspect provides a lithium ion secondary battery comprising the negative electrode for a lithium ion secondary battery of the above aspect, a positive electrode, and an electrolyte.
[0023] Effects of the Invention
[0024] A lithium ion secondary battery using the negative electrode active material for a lithium ion secondary battery of the embodiment described above has excellent cycle characteristics. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a result obtained by measuring the surface of the silicon particles of the first embodiment by X-ray photoelectron spectroscopy.
[0026] Figure 2It is a schematic diagram of the lithium ion secondary battery of the first embodiment.
[0027] Description of Reference Numerals
[0028] 10 Diaphragm
[0029] 20 positive electrode
[0030] 22Positive electrode collector
[0031] 24 Positive electrode active material layer
[0032] 30 negative electrode
[0033] 32 Negative electrode collector
[0034] 34 Negative electrode active material layer
[0035] 40 Power generation elements
[0036] 50 outer body
[0037] 52 metal foil
[0038] 54 resin layer
[0039] 60, 62 terminals
[0040] 100 Lithium-ion secondary battery DETAILED DESCRIPTION
[0041] Hereinafter, the embodiments will be described in detail with reference to the accompanying drawings as appropriate. In order to facilitate the understanding of the features, the drawings used in the following description sometimes enlarge the features for convenience, and sometimes the dimensional ratios of the components are different from the actual ones. The materials, dimensions, etc. illustrated in the following description are examples, and the present invention is not limited to these, and can be appropriately changed and implemented within the scope of not changing the purpose.
[0042] “Anode material”
[0043] The negative electrode material of the first embodiment is used for a lithium ion secondary battery and contains silicon particles. The negative electrode material of the first embodiment functions as, for example, a negative electrode active material.
[0044] The silicon particles are single silicon, silicon alloys, silicon compounds or silicon composites, and may be crystalline or amorphous.
[0045] Silicon alloys such as X n Si represents. X represents a cation. X is, for example, Ba, Mg, Al, Zn, Sn, Ca, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ge, Y, Zr, Nb, Mo, W, Au, Ti, Na, K, etc. n satisfies 0≤n≤0.5.
[0046] The silicon composite is, for example, a conductive material coated on at least a portion of the surface of particles of silicon or silicon compounds. The conductive material is, for example, a carbon material, Al, Ti, Fe, Ni, Cu, Zn, Ag, Sn, etc. For example, a silicon-carbon composite material (Si-C) is an example of a composite.
[0047] The silicon content of the silicon particles is, for example, not less than 97% and not more than 99%. The silicon content in the silicon particles can be measured, for example, by composition analysis using a transmission electron microscope (TEM). When using TEM, the distance from the center of the silicon particle to one-third of the particle radius is randomly measured, and the average value obtained by measuring more than 5 points is calculated. When the silicon content in the silicon particles is high, the capacity and initial efficiency of the lithium-ion secondary battery increase. In addition, when additives are mixed in the silicon particles, the volume expansion of silicon during charging and discharging of the lithium-ion secondary battery can be suppressed.
[0048] Silicon particles contain oxygen. Oxygen can also serve as a x The silicon oxide represented by is contained in the silicon particles. That is, a part of the silicon particles may be oxidized. For example, x satisfies 0.8≤x≤2.
[0049] The oxygen content of the silicon particles is, for example, 0.1 wt% to 8 wt%. The oxygen content of the silicon particles is the oxygen content of the entire silicon particles, and can be measured, for example, by an inert gas fusion-infrared absorption method. Before the measurement, as a pretreatment, a drying treatment is performed in a temperature range of 80°C to 100°C.
[0050] When silicon particles contain oxygen, lithium silicate is formed during the charge and discharge of a lithium-ion secondary battery. Lithium silicate is a SEI (solid electrolyte membrane) coating. The oxygen contained in the silicon particles affects the film quality of the SEI coating. Lithium silicate acts as a buffer material for expansion and contraction during the charge and discharge of a lithium-ion secondary battery. On the other hand, excessive lithium silicate becomes a resistor during charge and discharge, which may be the cause of reduced input and output characteristics of the lithium-ion secondary battery. If the oxygen content contained in the silicon particles is within the above range, an appropriate amount of lithium silicate is formed during the charge and discharge of the lithium-ion secondary battery.
[0051] For example, the silicon particles may have an oxide film on the surface. The oxygen constituting the oxide film is a part of the oxygen contained in the silicon particles. x The oxide film does not need to be entirely made of silicon oxide. For example, the oxide film may be entirely made of silicon oxide, or may contain residual silicon in part. The thickness of the oxide film is, for example, 50 nm to 500 nm, preferably 100 nm to 300 nm. The film thickness of the oxide film is, for example, the average value of the thickness of the oxide film formed on 100 silicon particles obtained from the cross-sectional image.
[0052] The oxide film on the surface of the silicon particles acts as a buffer for the volume expansion of the silicon particles during the charge and discharge of the lithium-ion secondary battery, thereby inhibiting the breakage of the silicon particles. In addition, if the thickness of the oxide film is below a certain value, the film resistance will not be too high, and the capacity of the lithium-ion secondary battery will increase.
[0053] The average particle size of the silicon particles is 0.1 μm to 10 μm, preferably 0.5 μm to 8 μm, and more preferably 1 μm to 7 μm. If the average particle size of the silicon particles is within the above range, the cycle characteristics are improved. If the silicon particles are too small, the contact area between the silicon particles and the electrolyte increases, and the risk of side reactions such as decomposition of the electrolyte increases. In addition, if the silicon particles are too large, the risk of side reactions such as decomposition of the electrolyte on the new surface generated by the damage of the silicon particles due to expansion and contraction increases.
[0054] When silicon particles can be obtained in a particle state, the median diameter (D50) can be obtained as the average particle diameter using a particle size distribution analyzer (for example, manufactured by Malvern Panalytical). When using a particle size distribution analyzer, for example, the average particle diameter of 50,000 particles is obtained.
[0055] When silicon particles are in the electrode and it is difficult to separate the silicon particles, the average particle size can be obtained using at least 100 silicon particles confirmed in the cross-sectional image. The average particle size measured using a particle size distribution analyzer and the average particle size obtained from the cross-sectional image are substantially consistent without much deviation.
[0056] First, silicon particles (negative electrode material) are extracted from the image by setting a contrast threshold and performing binarization. Then, the diameters of at least 100 extracted silicon particles are obtained respectively. The frequencies of the diameters of the obtained silicon particles are plotted, and the mode is set as the average particle size. In the case where the shape of the silicon particles is amorphous, the diameter of the major axis is used in the calculation of the average particle size.
[0057] The average circularity of the silicon particles is 0.80 to 0.99, preferably 0.910 to 0.988, and more preferably 0.920 to 0.985.
[0058] The average circularity of silicon particles is determined using the circularity of at least 100 silicon particles. The circularity is determined by dividing the circumference of a circle having the same area as the silicon particle to be measured by the circumference of the silicon particle to be measured.
[0059] The average circularity is the same as the average particle size. When silicon particles can be obtained in the form of particles, it can be obtained using a particle size distribution measuring device. When a particle size distribution measuring device is used, for example, the mode of the circularity of 50,000 particles is obtained. In addition, when the separation of silicon particles is difficult, the average circularity can be obtained using a cross-sectional image. When a cross-sectional image is used, for example, the circularity of each of 100 particles is obtained. Specifically, silicon particles are extracted from the image, and the circumference and area of each silicon particle are obtained. In addition, the circumference of a circle having the same area as the area of each silicon particle obtained is calculated, and the circularity of each silicon particle is calculated. Then, the mode of the circularity of the silicon particles is set as the average circularity. The average circularity measured using a particle size distribution measuring device and the average circularity obtained from the cross-sectional image do not deviate significantly and are roughly consistent.
[0060] The average aspect ratio of the silicon particles is 0.60 to 0.99, preferably 0.65 to 0.98, and more preferably 0.80 to 0.97.
[0061] The average aspect ratio of the silicon particles is obtained using the aspect ratios of at least 100 silicon particles. The aspect ratio is obtained by dividing the minor axis length of the silicon particles to be measured by the major axis length.
[0062] The average aspect ratio is the same as the average particle size. When silicon particles can be obtained in the form of particles, it can be obtained using a particle size distribution measuring device. When silicon particles are difficult to separate, it can be obtained using a cross-sectional image. When a particle size distribution measuring device is used, for example, the mode of the aspect ratios of 50,000 particles is obtained. When a cross-sectional image is used, for example, the mode of the aspect ratios of 100 particles is obtained. The average aspect ratio measured using a particle size distribution measuring device and the average aspect ratio obtained from the cross-sectional image do not deviate significantly and are roughly consistent.
[0063] Here, the silicon particles present in the electrode after the lithium ion secondary battery is charged and discharged are not necessarily consistent with the untreated silicon particles that can be obtained in the form of particles in terms of average particle size, average aspect ratio and average circularity. However, if the average particle size, average aspect ratio and average circularity obtained by any method meet the above range, the cycle characteristics of the lithium ion secondary battery are improved in the subsequent charge and discharge.
[0064] When the surface of the silicon particles is analyzed using X-ray photoelectron spectroscopy (XPS), a peak of SiO 2 and a peak of Si are confirmed. Figure 1The result obtained by measuring the surface of the silicon particles of the first embodiment by X-ray photoelectron spectroscopy. The XPS spectrum is a Si2p spectrum. The peak of SiO2 appears on the binding energy side higher than the peak of Si. For example, the peak of Si is confirmed between 96eV and 100eV in binding energy. For example, the peak of SiO2 is confirmed between 100eV and 104eV in binding energy. XPS measurement is measured, for example, using Quantera 2 manufactured by PHI.
[0065] When the surface of silicon particles is analyzed by X-ray photoelectron spectroscopy, the cumulative intensity ratio obtained by dividing the cumulative intensity of the peak of SiO2 by the cumulative intensity of the peak of Si is, for example, 0.4 to 3.0, preferably 0.6 to 1.5. The cumulative intensity refers to the height of the peak top when the cumulative number of XPS is set to 10 or more times.
[0066] In the surface analysis of silicon particles, for example, a lithium-ion secondary battery is decomposed, silicon particles are taken out, and the surface of the extracted silicon particles is measured. Alternatively, a lithium-ion secondary battery can be decomposed, the negative electrode is taken out, and the surface of the negative electrode is measured. In this case, information such as the binder is also detected, but it can be separated after the data is acquired.
[0067] The reason why the cycle characteristics of lithium-ion secondary batteries are improved when the cumulative intensity ratio obtained by X-ray photoelectron spectroscopy is within the above range is not clear. It is believed that the SiO2 present on a part of the surface of the silicon particles serves as a buffer material for the expansion and contraction of the lithium-ion secondary battery during charging and discharging and inhibits the damage of the silicon particles, the SiO2 present on a part of the surface of the silicon particles prevents direct contact between the electrolyte and silicon and inhibits the decomposition of the electrolyte, and the SiO2 present on a part of the surface of the silicon particles inhibits the generation of lithium silicate during charging and discharging.
[0068] In addition, when the inside of the silicon particles is analyzed using X-ray photoelectron spectroscopy, the cumulative intensity ratio obtained by dividing the cumulative intensity of the peak of SiO2 by the cumulative intensity of the peak of Si is, for example, 0.01 or more and 0.5 or less. The cumulative intensity ratio inside the silicon particles is different from the cumulative intensity ratio on the surface of the silicon particles. Compared with the surface of the silicon particles, the inside of the silicon particles can also be a silicon-rich state. When this structure is met, a lithium-ion secondary battery with high capacity and excellent cycle characteristics can be obtained.
[0069] The silicon particles used as the negative electrode material of the first embodiment can be produced, for example, by melting silicon and then solidifying it again. The molten silicon becomes round due to surface tension. The silicon particles used as the negative electrode material of the first embodiment can be produced, for example, by an atomization method or a thermal plasma method. However, depending on the conditions during production by these methods, the average particle size, average circularity, and average aspect ratio of the silicon particles vary. In order to shape the silicon particles into a prescribed shape, production conditions are set and controlled. Sometimes the production conditions have some deviations for each manufacturing device. Therefore, the actual production conditions are further determined by optimizing the production conditions through preliminary research.
[0070] The conditions for making silicon particles are as follows, for example. When using the thermal plasma method, silicon particles with an average particle size of 1 μm to 8 μm are melted as raw materials. The average particle size of the raw material is one of the parameters that affect the particle size of the silicon particles. In addition, as parameters that affect the shape of silicon particles, there are melting temperature, melting time, cooling temperature, cooling rate, etc. The melting temperature of silicon is, for example, set to 1200°C to 12000°C. The melting time of silicon is, for example, set to 1s to 300s. The cooling temperature when solidifying silicon is, for example, set to 15°C to 800°C. The cooling rate when solidifying silicon is, for example, set to 5°C / s to 10000°C / s. When the cooling rate is fast, the crystallinity of the particles decreases, the diffusion of lithium during charging and discharging tends to become uniform, and the cycle characteristics of the lithium-ion secondary battery are improved. The cooling rate is preferably 1000°C / s or more. In addition, the atmosphere when melting and cooling silicon is preferably an inert atmosphere such as Ar or nitrogen. In addition, when using a nozzle to introduce molten silicon into the cooling space, the diameter, shape, length of the nozzle, and the flow rate of molten silicon to the nozzle are designed. These also affect the shape of silicon particles. The diameter, shape, length, and flow rate of molten silicon to the nozzle are studied in advance to determine the conditions suitable for the device.
[0071] In addition, the silicon particles may also be subjected to an aging treatment. The aging treatment is a treatment in which the silicon particles are exposed to an environment with a humidity of 80% and a temperature of 25°C for a specified time or longer. The dew point during the aging treatment is set to 21°C, for example. As an atmosphere for the aging treatment, the oxygen concentration is preferably 20% or more. The aging treatment is performed slowly in an environment of weak ultraviolet irradiation intensity. The aging treatment can be performed using a fluorescent lamp or LED with an appropriate wavelength. In addition, by performing the aging treatment while periodically stirring or rotating the powder, the surface of the silicon particles is oxidized.
[0072] In addition, when making silicon particles, in order to adjust the ratio of SiO2 and Si on the silicon surface, the silicon particles are mixed and stirred in ethylene carbonate, water, or a mixture thereof. During the mixing and stirring, the surface of the silicon particles is oxidized. Degassed water is used, for example. By using degassed water, the degree of oxidation on the surface of the silicon particles can be adjusted. In addition, the degree of oxidation on the surface of the silicon particles can also be adjusted by the temperature during mixing and stirring, the stirring time, etc. The temperature during mixing and stirring is, for example, 45 degrees. The stirring time is, for example, set to more than 24 hours. In addition, the mixing and stirring is carried out in a weak ultraviolet environment using fluorescent lamps or LEDs. These lighting fixtures are added to the solution and stirred, for example.
[0073] The negative electrode material of the first embodiment has excellent cycle characteristics of the lithium ion secondary battery. This is believed to be because the silicon particles contain an appropriate amount of oxygen as SiO2, which inhibits the silicon particles from being damaged during charge and discharge of the lithium ion secondary battery and inhibits excessive decomposition of the electrolyte in contact with the silicon.
[0074] "Lithium-ion secondary battery"
[0075] Figure 2 It is a schematic diagram of the lithium ion secondary battery of the first embodiment. Figure 2 The lithium-ion secondary battery 100 shown in the figure includes a power generation element 40, an outer casing 50, and an electrolyte (for example, a non-aqueous electrolyte). The outer casing 50 surrounds the power generation element 40. The power generation element 40 is connected to the outside via a pair of terminals 60 and 62 connected to the power generation element 40. The non-aqueous electrolyte is contained in the outer casing 50. Figure 2 In the example, a case where one power generating element 40 is stacked in the exterior body 50 is illustrated, but a plurality of power generating elements 40 may be stacked.
[0076] (Power generation element)
[0077] The power-generating element 40 includes a separator 10, a positive electrode 20, and a negative electrode 30. The power-generating element 40 may be a stacked body in which these are stacked, or a wound body in which a structure in which these are stacked is wound.
[0078] <Positive electrode>
[0079] The positive electrode 20 includes, for example, a positive electrode current collector 22 and a positive electrode active material layer 24 . The positive electrode active material layer 24 is in contact with at least one surface of the positive electrode current collector 22 .
[0080] [Positive electrode collector]
[0081] The positive electrode current collector 22 is, for example, a conductive plate. The positive electrode current collector 22 is, for example, a thin metal plate such as aluminum, copper, nickel, titanium, or stainless steel. Lightweight aluminum is suitable for the positive electrode current collector 22. The average thickness of the positive electrode current collector 22 is, for example, not less than 10 μm and not more than 30 μm.
[0082] [Positive electrode active material layer]
[0083] The positive electrode active material layer 24 contains, for example, a positive electrode active material. The positive electrode active material layer 24 may contain a conductive auxiliary agent or a binder as necessary.
[0084] The positive electrode active material includes an electrode active material capable of reversibly absorbing and releasing lithium ions, desorbing and inserting (intercalating) lithium ions, or doping and dedoping lithium ions and counter anions.
[0085] The positive electrode active material is, for example, a composite metal oxide. Composite metal oxides include, for example, lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMnO2), lithium manganese spinel (LiMn2O4), and LiNiO2. x Co y Mn z M a O2 compounds (in the general formula, x+y+z+a=1, 0≤x<1, 0≤y<1, 0≤z<1, 0≤a<1, M is one or more elements selected from Al, Mg, Nb, Ti, Cu, Zn, Cr), lithium vanadium compounds (LiV2O5), olivine-type LiMPO4 (wherein M represents one or more elements selected from Co, Ni, Mn, Fe, Mg, Nb, Ti, Al, Zr or VO), lithium titanate (Li4Ti5O 12 )、LiNi x Co y Al z O2 (0.9<x+y+z<1.1). The positive electrode active material may also be an organic substance. For example, the positive electrode active material may also be polyacetylene, polyaniline, polypyrrole, polythiophene, or polyacene.
[0086] The positive electrode active material may also be a material that does not contain lithium. The material that does not contain lithium is, for example, FeF3, a conjugated polymer containing an organic conductive material, a Chevrel phase compound, a transition metal chalcogenide, a vanadium oxide, a niobium oxide, and the like. The material that does not contain lithium may be any one material alone, or a combination of multiple materials may be used. In the case where the positive electrode active material is a material that does not contain lithium, for example, discharge is first performed. Lithium is inserted into the positive electrode active material by discharge. In addition, the positive electrode active material may also be chemically or electrochemically pre-doped with lithium as a material that does not contain lithium.
[0087] The conductive additive improves the electronic conductivity between the positive electrode active materials. The conductive additive is, for example, carbon powder, carbon nanotubes, carbon materials, metal powder, a mixture of carbon materials and metal powder, and conductive oxides. Carbon powder is, for example, carbon black, acetylene black, Ketjen black, etc. Metal powder is, for example, powder of copper, nickel, stainless steel, iron, etc.
[0088] The content of the conductive aid in the positive electrode active material layer 24 is not particularly limited. For example, the content of the conductive aid relative to the total mass of the positive electrode active material, conductive aid, and binder is 0.5 mass % to 20 mass %, preferably 1 mass % to 5 mass %.
[0089] The binder in the positive electrode active material layer 24 binds the positive electrode active materials to each other. The binder can use a known binder. Preferably, the binder is insoluble in the electrolyte, has antioxidant properties, and has adhesive properties. The binder is, for example, a fluororesin. The binder is, for example, polyvinylidene fluoride (PVDF), polyvinyl alcohol (PVA), polytetrafluoroethylene (PTFE), polyamide (PA), polyimide (PI), polyamideimide (PAI), polybenzimidazole (PBI), polyether sulfone (PES), polyacrylic acid and its copolymers, metal ion crosslinked bodies of polyacrylic acid and its copolymers, polypropylene (PP) or polyethylene (PE) grafted with maleic anhydride, and mixtures thereof. The binder used for the positive electrode active material layer is particularly preferably PVDF.
[0090] The content of the binder in the positive electrode active material layer 24 is not particularly limited. For example, the content of the binder relative to the total mass of the positive electrode active material, the conductive aid, and the binder is 1% by mass or more and 15% by mass or less, preferably 1.5% by mass or more and 5% by mass or less. When the content of the binder is small, the bonding strength of the positive electrode 20 becomes weak. When the content of the binder is high, the binder is electrochemically inert and does not contribute to the discharge capacitance, so the energy density of the lithium ion secondary battery 100 becomes low.
[0091] <Negative electrode>
[0092] The negative electrode 30 includes, for example, a negative electrode current collector 32 and a negative electrode active material layer 34 . The negative electrode active material layer 34 is formed on at least one surface of the negative electrode current collector 32 .
[0093] [Negative electrode current collector]
[0094] The negative electrode current collector 32 is, for example, a conductive plate material. The negative electrode current collector 32 can be the same as the positive electrode current collector 22 .
[0095] [Negative Electrode Active Material Layer]
[0096] The negative electrode active material layer 34 includes a negative electrode active material and a binder. The negative electrode active material layer may also include a conductive additive, a dispersion stabilizer, etc. as needed. The negative electrode active material uses the above-mentioned negative electrode material. By using the above-mentioned negative electrode material as the negative electrode active material, the cycle characteristics of the lithium ion secondary battery 100 are improved.
[0097] The conductive additive and the binder can be the same as those of the positive electrode 20. The binder in the negative electrode 30 may be, for example, cellulose, styrene-butadiene rubber, ethylene-propylene rubber, polyimide resin, polyamide-imide resin, acrylic resin, etc., in addition to the substances mentioned in the positive electrode 20. Cellulose may be, for example, carboxymethyl cellulose (CMC).
[0098] <Diaphragm>
[0099] The separator 10 is sandwiched between the positive electrode 20 and the negative electrode 30. The separator 10 isolates the positive electrode 20 and the negative electrode 30 to prevent a short circuit between the positive electrode 20 and the negative electrode 30. The separator 10 is spread in a plane along the positive electrode 20 and the negative electrode 30. Lithium ions can pass through the separator 10.
[0100] The diaphragm 10 has, for example, an electrically insulating porous structure. The diaphragm 10 is, for example, a single layer or a laminate of a polyolefin film. The diaphragm 10 may also be a stretched film of a mixture of polyethylene or polypropylene. The diaphragm 10 may also be a fiber nonwoven fabric composed of at least one constituent material selected from cellulose, polyester, polyacrylonitrile, polyamide, polyethylene and polypropylene. The diaphragm 10 may also be, for example, a solid electrolyte. Solid electrolytes include, for example, polymer solid electrolytes, oxide-based solid electrolytes, and sulfide-based solid electrolytes. The diaphragm 10 may also be an inorganic coating diaphragm. The inorganic coating diaphragm is obtained by coating the surface of the above-mentioned film with a mixture of a resin such as PVDF or CMC and an inorganic substance such as alumina or silica. The inorganic coating diaphragm has excellent heat resistance and inhibits the precipitation of transition metals dissolved from the positive electrode to the surface of the negative electrode.
[0101] <Electrolyte>
[0102] The electrolyte is sealed in the outer casing 50 and impregnates the power generation element 40. The electrolyte is not limited to a liquid electrolyte, and may be a solid electrolyte. The non-aqueous electrolyte includes, for example, a non-aqueous solvent and an electrolytic salt. The electrolytic salt is dissolved in the non-aqueous solvent.
[0103] The solvent is not particularly limited as long as it is a solvent generally used for lithium ion secondary batteries. The solvent includes, for example, any one of a cyclic carbonate compound, a chain carbonate compound, a cyclic ester compound, and a chain ester compound. The solvent may also be included by mixing them in an arbitrary proportion. Cyclic carbonate compounds are, for example, ethylene carbonate (EC), propylene carbonate (PC), fluoroethylene carbonate, vinylene carbonate, etc. Chain carbonate compounds are, for example, diethyl carbonate (DEC), ethyl methyl carbonate (EMC), etc. Cyclic ester compounds are, for example, γ-butyrolactone, etc. Chain ester compounds are, for example, propyl propionate, ethyl propionate, ethyl acetate, etc.
[0104] The electrolytic salt is, for example, a lithium salt. The electrolyte is, for example, LiPF6, LiClO4, LiBF4, LiCF3SO3, LiCF3CF2SO3, LiC(CF3SO2)3, LiN(CF3SO2)2, LiN(CF3CF2SO2)2, LiN(CF3SO2)(C4F9SO2), LiN(CF3CF2CO)2, LiBOB, LiN(FSO2)2, etc. The lithium salt can be used alone or in combination of two or more. From the viewpoint of the degree of ionization, the electrolyte preferably contains LiPF6. The degree of dissociation of the electrolytic salt at room temperature in the carbonate solvent is preferably 10% or more.
[0105] The electrolyte is preferably an electrolyte obtained by dissolving LiPF6 in a carbonate solvent. The concentration of LiPF6 is, for example, 1 mol / L. When the polyimide resin contains a large amount of aromatics, the polyimide resin sometimes exhibits a charging behavior like soft carbon. When the electrolyte is a carbonate electrolyte solvent containing a cyclic carbonate, lithium and polyimide can be uniformly reacted. In this case, the cyclic carbonate is preferably ethylene carbonate, fluoroethylene carbonate, or vinylene carbonate.
[0106] <Exterior body>
[0107] The outer casing 50 seals the power generation element 40 and the non-aqueous electrolyte in its interior. The outer casing 50 prevents the non-aqueous electrolyte from leaking to the outside and preventing moisture from entering the lithium ion secondary battery 100 from the outside.
[0108] For example Figure 1 As shown, the outer package 50 includes a metal foil 52 and a resin layer 54 laminated on each surface of the metal foil 52. The outer package 50 is a metal laminate film in which the metal foil 52 is coated with a polymer film (resin layer 54) from both sides.
[0109] As the metal foil 52, for example, aluminum foil can be used. The resin layer 54 can utilize a polymer film such as polypropylene. The material constituting the resin layer 54 may be different on the inside and outside. For example, as the material of the outside, a polymer with a high melting point, such as polyethylene terephthalate (PET) and polyamide (PA), etc., can be used, and as the material of the polymer film on the inside, polyethylene (PE) and polypropylene (PP) can be used.
[0110] <Terminal>
[0111] Terminals 62 and 60 are connected to the positive electrode 20 and the negative electrode 30, respectively. The terminal 62 connected to the positive electrode 20 is a positive terminal, and the terminal 60 connected to the negative electrode 30 is a negative terminal. The terminals 60 and 62 are responsible for electrical connection with the outside. The terminals 60 and 62 are formed of conductive materials such as aluminum, nickel, and copper. The connection method can be welding or screwing. In order to prevent short circuits, it is preferred to protect the terminals 60 and 62 with insulating tape.
[0112] "Method for producing lithium-ion secondary battery"
[0113] The negative electrode 30, the positive electrode 20, the separator 10, the electrolyte solution, and the outer casing 50 are prepared separately and assembled to produce the lithium ion secondary battery 100. An example of a method for producing the lithium ion secondary battery 100 is described below.
[0114] The negative electrode 30 is produced, for example, by sequentially performing a slurry preparation step, an electrode coating step, a drying step, and a rolling step.
[0115] The slurry preparation process is a process of mixing the negative electrode active material, the binder, the conductive aid and the solvent to prepare the slurry. The negative electrode active material uses the negative electrode material mentioned above. When a dispersion stabilizer is added to the slurry, the aggregation of the negative electrode active material can be suppressed.
[0116] The slurry preparation process is a process for preparing slurry by mixing a negative electrode active material, a binder, a conductive aid and a solvent. The solvent is, for example, water, N-methyl-2-pyrrolidone, etc. The composition ratio of the negative electrode active material, the conductive material and the binder is preferably 70wt% to 100wt%: 0wt% to 10wt%: 0wt% to 20wt% in terms of mass ratio. Their mass ratio is adjusted to be 100wt% as a whole. The container used when making the slurry is preferably a metal container such as SUS. When a polar solvent such as N-methyl-2-pyrrolidone is used as the solvent, the electrostatic capacitance of the oxide film on the surface of the silicon particles becomes larger. The polar solvent prevents the repulsion of the conductive aid and the silicon particles. By suppressing these repulsions, the capacity of the lithium-ion secondary battery can be prevented from decreasing.
[0117] The negative electrode active material may also be a material obtained by mixing active material particles and conductive materials while applying shear force to form a composite. When the active material particles are mixed by applying shear force to a degree that does not deteriorate, the surface of the active material particles is coated with the conductive material. In addition, the particle size of the negative electrode active material can be adjusted according to the degree of mixing. In addition, the negative electrode active material after production can also be screened to make the particle size uniform.
[0118] The electrode coating step is a step of coating the slurry on the surface of the negative electrode current collector 32. The method for coating the slurry is not particularly limited. For example, a slit die coating method or a doctor blade method can be used as the slurry coating method. The slurry is coated at room temperature, for example.
[0119] The drying step is a step of removing the solvent from the slurry. For example, the negative electrode current collector 32 coated with the slurry is dried in an atmosphere at 80°C to 350°C.
[0120] The rolling step is performed as necessary. The rolling step is a step of applying pressure to the negative electrode active material layer 34 to adjust the density of the negative electrode active material layer 34. The rolling step is performed by, for example, a roll press device or the like.
[0121] The positive electrode 20 can be produced in the same procedure as the negative electrode 30. As the separator 10 and the outer casing 50, commercially available products can be used.
[0122] Next, the positive electrode 20 and the negative electrode 30 are stacked so that the separator 10 is located between them to produce the power generation element 40. When the power generation element 40 is a wound body, the positive electrode 20, the negative electrode 30 and the separator 10 are wound around one end side of the axis.
[0123] Finally, the power generation element 40 is sealed in the outer body 50. The non-aqueous electrolyte is injected into the outer body 50. After the non-aqueous electrolyte is injected, the non-aqueous electrolyte is impregnated in the power generation element 40. By applying heat and the like and sealing the outer body 50, the lithium ion secondary battery 100 is obtained. In addition, the electrolyte may not be injected into the outer body 50, but the power generation element 40 may be impregnated in the electrolyte. It is preferred to leave the power generation element 40 to stand for 24 hours after the electrolyte is injected.
[0124] The lithium ion secondary battery 100 according to the first embodiment has excellent cycle characteristics because the negative electrode active material includes a predetermined negative electrode material.
[0125] Although the embodiments of the present invention have been described in detail with reference to the drawings, each structure of each embodiment and their combination are merely examples, and addition, omission, replacement, and other changes to the structure may be made without departing from the spirit of the present invention.
[0126] Example
[0127] "Example 1"
[0128] The positive electrode slurry was applied to one side of an aluminum foil having a thickness of 15 μm. The positive electrode slurry was prepared by mixing a positive electrode active material, a conductive auxiliary agent, a binder, and a solvent.
[0129] The positive electrode active material uses Li x CoO2. Acetylene black was used as a conductive aid. Polyvinylidene fluoride (PVDF) was used as a binder. N-methyl-2-pyrrolidone was used as a solvent. 97 parts by mass of a positive electrode active material, 1 part by mass of a conductive aid, 2 parts by mass of a binder, and 70 parts by mass of a solvent were mixed to prepare a positive electrode slurry. The amount of positive electrode active material in the dried positive electrode active material layer was set to 25 mg / cm 2 The solvent was removed from the positive electrode slurry in a drying furnace to produce a positive electrode active material layer. The positive electrode active material layer was pressed by roll pressing to produce a positive electrode.
[0130] Next, a negative electrode slurry was prepared. The negative electrode active material added to the negative electrode slurry used silicon particles with an average particle size of 4.6μm, an average circularity of 0.954, and an average aspect ratio of 0.91. The silicon particles were mixed and stirred in a mixture of ethylene carbonate and water at 45°C for 24 hours. In addition, LEDs were added to the solution and mixed and stirred under a weak ultraviolet environment. The average particle size, average circularity, and average aspect ratio were obtained by measuring 50,000 particles using a particle size distribution meter manufactured by Malvern Panalytical. As an aging treatment, it was exposed for 7 days in an environment of 25°C and 80% humidity. An oxide film with an average thickness of 221nm was formed on the surface of the exposed silicon particles.
[0131] Carbon black was used as a conductive aid. Polyimide resin was used as a binder. N-methyl-2-pyrrolidone was used as a solvent. 90 parts by mass of a negative electrode active material, 5 parts by mass of a conductive aid, and 5 parts by mass of a binder were mixed with N-methyl-2-pyrrolidone to prepare a negative electrode slurry.
[0132] Then, the negative electrode slurry was applied to one side of a copper foil having a thickness of 10 μm, and the slurry was dried. The amount of negative electrode active material supported in the negative electrode active material layer after drying was set to 2.5 mg / cm 2 The negative electrode active material layer was pressed by roll pressing and then sintered at 300° C. or higher for 5 hours in a nitrogen atmosphere.
[0133] Next, an electrolyte was prepared. The solvent of the electrolyte was set to fluoroethylene carbonate (FEC): ethylene carbonate (EC): diethyl carbonate (DEC) = 10 volume %: 20 volume %: 70 volume %. In addition, output-enhancing additives, gas-suppressing additives, cycle characteristics-improving additives, safety performance-improving additives, etc. were added to the electrolyte. LiPF6 was used as the electrolytic salt. The concentration of LiPF6 was set to 1 mol / L.
[0134] (Preparation of lithium-ion secondary battery for evaluation)
[0135] The produced negative electrode and positive electrode are stacked with a separator (porous polyethylene sheet) in a manner that the positive electrode active material layer and the negative electrode active material layer are opposite to each other to obtain a stack. The stack is inserted into the outer body of the aluminum laminate film and heat-sealed except for one part around it to form a closed portion. Moreover, finally, after injecting the above-mentioned electrolyte into the outer body, the remaining part is sealed by heat sealing while reducing the pressure using a vacuum sealer, thereby producing a lithium ion secondary battery. The manufactured lithium ion secondary battery is left to stand for 24 hours.
[0136] (Determination of capacity maintenance rate after 300 cycles)
[0137] The cycle characteristics of the lithium ion secondary battery were measured using a secondary battery charge and discharge tester (manufactured by Hokuto Denko Co., Ltd.).
[0138] The battery was charged at a constant current rate of 1C (the current value at which charging is completed within 1 hour at 25°C) until the battery voltage reached 4.2V, and discharged at a constant current rate of 1.0C until the battery voltage reached 2.5V. The discharge capacitance after the charge and discharge was detected to obtain the battery capacity Q1 before the cycle test. The battery capacity Q1 was 3650mAh / g.
[0139] The battery whose battery capacity Q1 has been obtained above is used again in a secondary battery charge and discharge test device, and is charged at a constant current charge rate of 1C until the battery voltage becomes 4.2V, and is discharged at a constant current discharge rate of 1C until the battery voltage becomes 2.5V. The above charge and discharge are counted as one cycle, and 300 cycles of charge and discharge are performed. Then, the discharge capacitance after 300 cycles of charge and discharge is detected, and the battery capacity Q2 after 300 cycles is obtained. Based on the battery capacities Q1 and Q2 obtained above, the capacity retention rate E after 300 cycles is obtained. The capacity retention rate E is obtained as E=Q2 / Q1×100. The capacity retention rate of Example 1 is 97%.
[0140] "Examples 2 to 17"
[0141] In Examples 2 to 17, the average particle size, average circularity, average aspect ratio, cumulative intensity ratio of SiO2 peak and Si peak, thickness of oxide film and oxygen content of silicon particles used as negative electrode active material were changed, which are different from Example 1. The average particle size, average circularity and average aspect ratio of silicon particles are controlled by changing the melting conditions and cooling conditions when making silicon particles. The thickness and oxygen content of the oxide film of silicon particles are controlled by changing the aging treatment time. The cumulative intensity ratio of SiO2 peak and Si peak is controlled by changing the time and temperature of mixing and stirring silicon particles in a mixture of ethylene carbonate and water.
[0142] "Comparative Examples 1 to 8"
[0143] In Examples 1 to 6, the average particle size, average circularity, average aspect ratio, cumulative intensity ratio of SiO2 peak and Si peak, thickness of oxide film and oxygen content of silicon particles used as negative electrode active material were changed, which are different from Example 1. The average particle size, average circularity and average aspect ratio of silicon particles are controlled by changing the melting conditions and cooling conditions when making silicon particles. The thickness and oxygen content of the oxide film of silicon particles are controlled by changing the aging treatment time. The cumulative intensity ratio of SiO2 peak and Si peak is controlled by changing the time and temperature of mixing and stirring silicon particles in a mixture of ethylene carbonate and water.
[0144] The results of Examples 1 to 17 and Comparative Examples 1 to 8 are summarized in Tables 1 and 2 below.
[0145] [Table 1]
[0146]
[0147] [Table 2]
[0148]
[0149] Compared with Comparative Examples 1 to 8, Examples 1 to 19 have high capacity retention rates and excellent cycle characteristics.
[0150] In Comparative Example 1, the average particle size of silicon particles is small and the contact area with the electrolyte is large. Therefore, it is believed that in Comparative Example 1, lithium is consumed in the irreversible reaction (side reaction) between silicon and the electrolyte, and the capacity retention rate becomes low. In Comparative Example 2, the average particle size of silicon particles is large. It is believed that large silicon particles are easily broken when expanding and shrinking, and the capacity retention rate of Comparative Example 2 becomes low.
[0151] In Comparative Examples 3 to 8, the cumulative intensity ratio obtained by dividing the cumulative intensity of the peak of SiO2 by the cumulative intensity of the peak of Si is outside the prescribed range. The reason why the cycle characteristics of the lithium-ion secondary battery are reduced when the cumulative intensity ratio is outside the prescribed range is not clear. However, the cycle characteristics of Comparative Examples 3 to 7 are all half the degree of Examples 1 to 17 in which the cumulative intensity ratio is within the prescribed range.
Claims
1. A negative electrode material for a lithium ion secondary battery, wherein: Contains silicon particles, The average particle size of the silicon particles is 0.1 μm to 10 μm, and the oxygen content is 0.1 wt% to 8 wt%. When the surface of the silicon particles is analyzed using X-ray photoelectron spectroscopy, the integrated intensity ratio obtained by dividing the integrated intensity of the SiO 2 peak by the integrated intensity of the Si peak is 0.4 to 3.
0.
2. The negative electrode material for lithium ion secondary battery according to claim 1, wherein The cumulative intensity ratio is greater than or equal to 0.6 and less than or equal to 1.
5.
3. The negative electrode material for lithium ion secondary battery according to claim 1, wherein The silicon particles have an average circularity of 0.920 to 0.985, and an average aspect ratio of 0.80 to 0.
97.
4. The negative electrode material for lithium ion secondary battery according to claim 1, wherein The silicon particles have an oxide film on the surface. The oxide film has a thickness of 50 nm to 500 nm.
5. The negative electrode material for lithium ion secondary battery according to claim 4, wherein The oxide film has a thickness of not less than 100 nm and not more than 300 nm.
6. The negative electrode material for lithium ion secondary battery according to claim 1, wherein The average particle size of the silicon particles is 1 μm or more and 7 μm or less.
7. The negative electrode material for lithium ion secondary battery according to claim 1, wherein The silicon content of the silicon particles is 97% or more and 99% or less.
8. A negative electrode for a lithium ion secondary battery, in, The negative electrode material for a lithium ion secondary battery according to claim 1 is included.
9. A lithium ion secondary battery, wherein: The invention comprises the negative electrode for lithium ion secondary battery according to claim 8, a positive electrode, and an electrolyte.
Citation Information
Patent Citations
Negative electrode for lithium ion secondary battery and lithium ion secondary battery
JP2019149333A